2019
DOI: 10.3389/fnut.2019.00116
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Early Vitamin D Concentrations and Gestational Diabetes Mellitus in Indian Pregnant Women

Abstract: Background: A high prevalence of vitamin D deficiency exists in pregnant Indian women (~90%). Increasing evidence suggests that vitamin D could play a pivotal role in maintaining normal glucose homeostasis. We aimed to determine the association between maternal vitamin D concentrations in early pregnancy and the risk of gestational diabetes mellitus (GDM). Methods: A prospective observational study was conducted on healthy pregnant women ( n = 392) atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 42 publications
6
18
0
Order By: Relevance
“…This is in line with findings of a recent large case‐control study among a cohort (116 GDM cases and 303 controls) of pregnant women in neighboring Saudi Arabia, which reported that women with vitamin D deficiency in early pregnancy had a 2.87 higher risk of subsequent GDM 11 . As mentioned above, several studies showed a significant association between GDM and vitamin D deficiency/vitamin D level 7–11 . Moreover, a recent meta‐analysis of 20 studies including 9209 participants reported that pregnant women who had vitamin D deficiency had a significantly increased risk for GDM 19 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is in line with findings of a recent large case‐control study among a cohort (116 GDM cases and 303 controls) of pregnant women in neighboring Saudi Arabia, which reported that women with vitamin D deficiency in early pregnancy had a 2.87 higher risk of subsequent GDM 11 . As mentioned above, several studies showed a significant association between GDM and vitamin D deficiency/vitamin D level 7–11 . Moreover, a recent meta‐analysis of 20 studies including 9209 participants reported that pregnant women who had vitamin D deficiency had a significantly increased risk for GDM 19 .…”
Section: Discussionsupporting
confidence: 88%
“…Published evidence on the relationship between vitamin D level and the occurrence of GDM is not yet conclusive. Many studies have shown a significant association between GDM and vitamin D level, 7–11 but other studies have shown no significant difference in this level between women with GDM and a control group of women 12–15 . Moreover, there are no published data on the association between vitamin D levels and GDM in Africa (including Sudan).…”
Section: Introductionmentioning
confidence: 99%
“…Our ndings are similar to some previous studies that investigated vitamin D status and the GDM risk [20][21][22][23], and the nding from three separate meta-analyses of published studies [24][25][26], which reported 38-61% higher risk of GDM among women with vitamin D deciency [18,19,26]. Recently, Pratibha Dwarkanath et al have reported that lower vitamin D concentrations in early pregnancy may be associated with a higher risk of developing GDM [21]. Furthermore, a study conducted in Saudi Arabia has concluded the development of GDM among pregnant women having decient vitamin D status [22].…”
Section: Discussionsupporting
confidence: 91%
“…Globally, vitamin D deficiency has been identified during pregnancy, but it is not clear whether or not this is physiological [28][29][30][31][32]. Some studies proved that low plasma vitamin D rates in the first 28 weeks of amenorrhea may be correlated to a higher risk of developing diabetes after the second trimester of pregnancy [33]. In everyday practice 25-[OH]D is tested, which is a free fraction that during pregnancy reaches the cells and is transformed into an activated hormone through a placenta receptor by placenta 1-alpha-hydroxylase enzyme [34].…”
Section: Resultsmentioning
confidence: 99%